On the asymptotic expansions for the probabilities of large deviations - Saulis, L. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. Саулис. Асимптотическое разложение для вероятностей больших уклонений L. Saulis. Didelių nukrypimų tikimybių asimptotinis išdėstymas